The influence of the structure area on the performance of SHM systems based on E/M impedance - Baptista, F. [UNESP]; Filho, J. V. [UNESP] (My University, 2009)
Piezoelectric transducers of PZT (lead zirconate titanate) have been widely used in structural health monitoring (SHM) systems based on the electromechanical (E/M) impedance technique and many studies indicate the efficiency of PZT to detect structural damages. However, some practical considerations still have to be considered in real applications. In this work, the goal was to evaluate the effect of the cross-section area of the monitored structure. Tests show that SHM based on E/M impedance is less efficient when the monitored structure has large cross-section area.